Introduction - Zachariadis, Theodoros (My University, 2012)
Transportation is a major contributor to global energy consumption and greenhouse gas (GHG) emissions, accounting for about one fourth of total energy-related carbon dioxide (CO2) emissions worldwide. Together with power generation, it is the fastest growing sector in the world. But unlike power generation, whose emissions may be easier to control because they come from a few thousand power plants around the world and because low-carbon or zero-carbon energy sources are already available on a large scale, transport emissions are created by the individual tailpipes of more than one billion motor vehicles (mostly passenger cars) as well as from fuel combustion in airplanes and ships, depending almost entirely on petroleum products with still limited low-carbon alternatives. The global car population is projected to exceed two billion by the year 2050, mainly due to increased car ownership in China, India and other rapidly growing economies (IEA 2009, Sperling and Gordon 2010). And car travel is among the economic activities that are least responsive to price changes: increased mobility improves the standard of living, and automobiles are associated with freedom and comfort. Most citizens of the world wish to have the opportunity to use a car – but can this wish be made compatible with the increasingly strained carrying capacity of the earth and the associated climate challenges?
Keywords: European Union; Climate policy; Fuel economy; European Union Policy; Sustainable mobility